Impact of Periodic Cycling on Lithium Battery Performance in Standby UPS Systems: A Case Study of a Vertiv 100 kW - Sithole, Tshepo; Sumbwanyambe, Mbuyu (International Journal of Electrical, Energy and Power System Engineering, 2026)
Lithium Iron Phosphate batteries in standby uninterruptible power supply (UPS) applications are susceptible to calendar aging when infrequently cycled, yet empirical field data on performance recovery strategies for large-scale industrial systems remain scarce. This study investigates the performance degradation of a Vertiv 100 kW three-phase UPS paired with two strings of 8 Vision Lithium batteries (100 Ah, 52.4 Vdc each), installed in 2021 at a commercial facility with a stable 45 kW load. After three years of minimal cycling, clients reported reduced backup duration, intermittent battery alarms, and DC breaker trips, attributed to calendar aging effects including elevated internal resistance and capacity fade under prolonged high state-of-charge conditions. A manual discharge/recharge protocol was implemented twice weekly using the site load, with discharge duration recorded across successive cycles. Battery performance recovered progressively, with discharge time increasing from 3 minutes to 18 minutes over 10 cycles, corresponding to a State of Health improvement from 2.68% to 16.10%. Following this recovery, the system was programmed for automatic periodic discharges. These findings demonstrate that periodic cycling effectively mitigates calendar aging in standby LFP systems and provide a practical framework for preventive battery management in low-outage industrial UPS environments.